2014
DOI: 10.1364/oe.22.014757
|View full text |Cite
|
Sign up to set email alerts
|

Morphology effect on the light scattering and dynamic response of polymer network liquid crystal phase modulator

Abstract: Polymer network liquid crystal (PNLC) was one of the most potential liquid crystal for submillisecond response phase modulation, which was possible to be applied in submillisecond response phase only spatial light modulator. But until now the light scattering when liquid crystal director was reoriented by external electric field limited its phase modulation application. Dynamic response of phase change when high voltage was applied was also not elucidated. The mechanism that determines the light scattering was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Previous studies have reported that THz wave phase shifters using LC have either a tiny phase change 17) or a excessively long decay time due to the thick LC layer of several hundreds of micrometers or more. [18][19][20][21] As effective methods for improving the decay time, polymerstabilized LC (PSLC) [22][23][24][25][26][27][28][29][30] and nanofiber (NF)/LC composite 31,32) have been employed. In the PSLC, reactive bifunctional monomers with a small amount (<10 wt%) are mixed into the LC and crosslinked to each other after polymerization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that THz wave phase shifters using LC have either a tiny phase change 17) or a excessively long decay time due to the thick LC layer of several hundreds of micrometers or more. [18][19][20][21] As effective methods for improving the decay time, polymerstabilized LC (PSLC) [22][23][24][25][26][27][28][29][30] and nanofiber (NF)/LC composite 31,32) have been employed. In the PSLC, reactive bifunctional monomers with a small amount (<10 wt%) are mixed into the LC and crosslinked to each other after polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…33) However, previous studies have reported that the PSLC threshold voltage rises by several tens of volts, even in the thickness of only a few tens of micrometers. 25,26,29) In another example for a device at THz frequency, where the decay time was significantly shortened to a few tens of milliseconds, an enormous voltage of approximately 900 V was employed to obtain a phase change of 30°. At that time, the composite showed 55% of the natural ability in the THz birefringence of LC.…”
Section: Introductionmentioning
confidence: 99%